Field report PAC 671: Cheng Hua Engineering Works Sdn. Bhd / Nur Irdyna Sofea Rosli - Rosli, Nur Irdyna Sofea (Universiti Teknologi MARA, Terengganu, 2024)
Cheng Hua Engineering Works Sdn Bhd was established in 1968 and has continuously advanced and created material handling solutions for global enterprises. This has enabled the company to adjust and expand into its current state. Cheng Hua's efforts have allowed it to successfully expand into a number of other countries, including China, Indonesia, India, and Thailand. Consequently, this drove them to become a globally recognized and influential system integrator that fulfills the need for advanced turnkey solutions in industrial automation, material handling, and logistics.